Prevalence of human parechovirus and enterovirus in cerebrospinal fluid samples in children in Jinju, Korea - Ji-Hyun Seo; Jung Sook Yeom; Hee-Shang Youn; Tae-Hee Han; Ju-Young Chung (Korean Pediatric Society, 2015)
PurposeHuman parechovirus (HPeV) and enterovirus (EV) are causative agents of a sepsis-like illness in neonates and of infections of the central nervous system in young children. The objectives of this study were to assess the prevalence of HPeV3 and EV infection in young children with a sepsis-like illness or with meningitis in Jinju, Korea.MethodsCerebrospinal fluid (CSF) samples were collected from 267 patients (age range, 1 day to 5 years) and assessed for HPeV and EV by performing reverse transcription polymerase chain reaction assay. Amplification products of the VP3/VP1 region of HPeV and of the VP1 region of EV were sequenced to identify the virus type.ResultsHPeV and EV were detected in 3.4% and 7.5% of the total CSF samples assessed, respectively. The age distribution of EV-positive patients (median age, 1.4 months) had a significantly broader range than that of HPeV-positive patients (median age, 7.8 months). The peak seasons for HPeV and EV infection were spring and summer, respectively. The clinical symptoms for HPeV and EV infection were similar, and fever was the most common symptom. Pleocytosis was detected in 22.2% of HPeV-positive patients and 35.5% of EV-positive patients. The VP3/VP1 gene sequence of the nine Korean strains clustered most closely with the Japanese strain (AB759202).ConclusionThe data indicate that HPeV infection is predominant in young infants (<6 months) and that meningitis without pleocytosis was caused by both HPeV and EV infection in children.